Cost-efficient pathways to decarbonizing Portland cement production - Gunther Glenk; Anton Kelnhofer; Rebecca Meier; Stefan Reichelstein (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2023)
Accounting for nearly 8% of global annual carbon dioxide (CO2) emissions, the cement industry is considered difficult to decarbonize. While a sizeable number of abatement levers for Portland cement production are technologically ready for deployment, many are still viewed as prohibitively expensive. Here we develop a generic abatement cost framework for identifying cost-efficient pathways toward substantial emission reductions. We calibrate our model with new industry data in the context of European cement plants that must obtain emission permits under the European Emission Trading System. We find that a price of exteuro81 per ton of CO2, as observed on average in 2022, incentivizes firms to reduce their annual direct emissions by about one-third relative to the status quo. Yet, this willingness to abate emissions increases sharply at a carbon price of exteuro100 per ton. If cement producers were to expect such carbon price levels to persist in the future, they would have incentives to reduce emissions by almost 80% relative to current emission levels.
Keywords: M1; O33; Q42; Q52; Q54; Q55; Q58; 330; marginal abatement cost; carbon emissions; industrial decarbonization; cement production